IMPLEMENTATION OF MAQASHID SHARI'AH AS THE FOUNDATION OF ISLAMIC ECONOMIC SYSTEM FROM AL-SYATIBI PERSPECTIVE (International Conference on Social and Islamic Studies, 2022)
A big challenge faced by Muslims today is the alignment of Islamic ideology with various aspects of human life, especially the economic aspect which is a vital point of human life. Through religious ideology, Muslims are encouraged to be able to answer various problems that occur in the midst of life. Therefore, Maqashid shari'ah has become very essential in Islamic economics and occupies a place. The shari'ah perspective views that the reason humans are involved in economic activity is an effort to maintain the mashlahah. Economic activity, both production and consumption, must be based on the principle of mashlahah. All forms of economic activity that bring mashlahah to humans are about needs that must be met, not activities oriented to the satisfaction of wants. This is a goal in economic activity as well as a religious obligation Islamic economics places Maqashid shari’ah as the foundation, so that the economic system and science that is run can provide mashlahah and be able to be a solution to any economic problems that occur. Al-Syatibi's thought in the field of economics is known for its ability to connect the Maqashid Shari’ah concept as the foundation of the Islamic economic system such as the concept of property ownership, reproductive needs, taxation, consumption, distribution and fiscal policy.